2022
DOI: 10.3390/jcm11133697
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cardiac Autonomic Responses with Clinical Outcomes of Myasthenia Gravis: Short-Term Analysis of the Heart-Rate and Blood Pressure Variability

Abstract: Introduction: The aim of the study was to assess cardiac and autonomic function in patients with myasthenia gravis (MG) and to explore its relationship with disease outcomes. Methods: Thirty-eight patients with an MG were enrolled (median age 40.5 years; median disease duration 5.5 years). Cardiovascular parameters, baroreflex sensitivity (BRS), spectral indices of short-term heart rate (HRV), and systolic blood pressure variability (SBPV) were compared with age- and gender-matched controls (n = 30). Cardiac a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…The on-call resident and the attending physician were consulted: Metoprolol was decreased from 50 to 25 mg daily; later, the PCP discontinued the med and referred Brian to cardiology (https://www. myaware.org/drugs-to-avoid; (Zawadka-Knuikowska et al, 2022). -Medication on healthcare record was not changed when the PCP increased glipizide from 20 to 40 mg daily.…”
Section: Key Practice Pointsmentioning
confidence: 99%
“…The on-call resident and the attending physician were consulted: Metoprolol was decreased from 50 to 25 mg daily; later, the PCP discontinued the med and referred Brian to cardiology (https://www. myaware.org/drugs-to-avoid; (Zawadka-Knuikowska et al, 2022). -Medication on healthcare record was not changed when the PCP increased glipizide from 20 to 40 mg daily.…”
Section: Key Practice Pointsmentioning
confidence: 99%
“…Response to Tilt: LF tilt , HF tilt , LF/HF tilt , LF/HF tilt of HRV, PSD tilt Data pooled from two studies [10,11] including 68 subjects with MG and 60 HCs demonstrated that patients with MG had a lower HF-RRI during tilt (g = −0.75, 95% CI −0.11-−0.39, p < 0.001). There was no heterogeneity (I 2 = 0; p = 0.98).…”
Section: Frequency Domain Hrv Parameters Inmentioning
confidence: 99%
“…The concept of cardiac involvement in MG was presented for the first time in 1901 when Bramwell described a 30-year-old male myasthenic patient who had tachycardia and heart failure, and defined it as cardiomyasthenia [5]. Since then, research has described myositis and/or myocarditis, conduction and diastolic left ventricle abnormalities, and cardiac autonomic dysfunction (CAD) in MG [6][7][8][9][10][11][12][13][14][15][16][17]. CAD has remained poorly characterized, probably due to subclinical forms and the lack of routine cardiac autonomic evaluation in MG patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the cardiac dysfunction was also associated with MG. Dysfunction of the cardiac autonomic nervous system with predominant parasympathetic impairment might lead to abnormal baroreflex sensitivity, as well as heart-rate and blood-pressure variability [ 2 , 3 , 4 ]. Recently, myocardial injury was also reported in patients with MG [ 5 ].…”
Section: Introductionmentioning
confidence: 99%